Numerical Analysis of Wave Load Characteristics on Jack-Up Production Platform Structure Using Modified k-ω SST Turbulence Model - Gilang Muhammad; Arini, Nu Rhahida; Ilman, Eko Charnius; Ariwibowo, Teguh Hady (Politeknik Elektronika Negeri Surabaya (PENS), 2023)
One of the important stages in the offshore structure design process is the evaluation of the marine hydrodynamic load in which the structure operates, this is to ensure an appropriate design and improve the safety of the structure. Therefore, accurate modeling of the marine environment is needed to produce good evaluation data, one of the methods that can accurately model the marine environment is through the Computational Fluid Dynamic (CFD) method. This research aims to analyze the ocean wave load of pressure and force characteristics on the jack-up production platform hull structure using the (CFD) method. The foam-extend 4.0 (the fork of the OpenFOAM) software with waveFoam solver is utilized to predict the free surface flow phenomena as its capability to predict with accurate results. The Reynold Averaged Navier Stokes (RANS) turbulence model of k-ω SST is applied to predict the turbulence effect in the flow field. Five variations of incident wave direction type are carried out to examine its effect on the pressure and force characteristics on the jack-up production platform hull. The wave model shows inaccurate results with the decrease in wave height caused by excessive turbulence in the water surface area. Excessive turbulence levels can be overcome by incorporating density variable and buoyancy terms based on the Standard Gradient Diffusion Hypothesis (SGDH) into the turbulent kinetic energy equation. The k-ω SST Buoyancy turbulence model shows accurate results when verified to predict wave run-up and horizontal force loads on monopile structures. Furthermore, test results of the wave load on the jack-up production platform hull structure shows that the most significant wave load is obtained in variations with the wave arrival direction relatively opposite to the platform wall. Especially in the direction of 90° because it also has the most expansive impact surface area. Meanwhile, the lower wave load is obtained in variations 45° and 135°, which have the relatively oblique direction of wave arrival to the surface.